2006
DOI: 10.2172/894989
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Pyrolysis Oil Production: A Technology Assessment and Economic Analysis

Abstract: Executive SummaryPyrolysis is one of a number of possible paths for converting biomass to higher value products. As such, this technology can play a role in a biorefinery model to expand the suite of product options available from biomass. The intent of this report is to provide the reader with a broad perspective of pyrolysis technology as it relates to converting biomass substrates to a liquid "bio oil" product, and a detailed technical and economic assessment of a fast pyrolysis plant producing 16 tonne/day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
250
1
9

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 241 publications
(264 citation statements)
references
References 38 publications
4
250
1
9
Order By: Relevance
“…However, they require energy to fluidize the system or provide cyclonic motion and tend to result in large amounts of char and ash fines comingled with the product stream. Mineral content of the pyrolysis oils is believed to relate to the stability of the product (Ringer et al, 2006). This is typically mitigated with cyclonic separators at the exit of the furnace, requiring additional energy, yet still allowing some particle pass-through.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, they require energy to fluidize the system or provide cyclonic motion and tend to result in large amounts of char and ash fines comingled with the product stream. Mineral content of the pyrolysis oils is believed to relate to the stability of the product (Ringer et al, 2006). This is typically mitigated with cyclonic separators at the exit of the furnace, requiring additional energy, yet still allowing some particle pass-through.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The experimental section to this report focuses on the prospects for the gases based on analysis of a bench-scale system. The end use of the liquids is not well studied, although it is suggested that the oils can substitute for fuel oils, be upgraded to petroleum equivalent fuels, or be used as tars in asphalt (see for example Czernik andBridgwater, 2004 andRinger et al, 2006 who review end uses of the product). Solids are essentially charcoal-like material.…”
Section: Figure 1 a Diagram Of The Proposed Processmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, its application for electricity generation is still in an infant stage. In the areas of internal combustion engines and aeroderivative turbines, quality issues remain a challenge (Ringer et al 2006). This may be overcome through deoxygenation of most of the chemical species present in the oil.…”
Section: Introductionmentioning
confidence: 99%